Regioselectivity in the ring opening of non-activated aziridines - Stanković, Sonja; D'hooghe, Matthias; Catak, Saron; Eum, Heesung; Waroquier, Michel; Van Speybroeck, Veronique; De Kimpe, Norbert; Ha, Hyun-Joon (Chemical Society reviews, 2012)
In this critical review, the ring opening of non-activated 2-substituted aziridines via intermediate aziridinium salts will be dealt with. Emphasis will be put on the relationship between the observed regioselectivity and inherent structural features such as the nature of the C2 aziridine substituent and the nature of the electrophile and the nucleophile. This overview should allow chemists to gain insight into the factors governing the regioselectivity in aziridinium ring openings (81 references).